Understanding SFRA Results using Transformer Model with Simulated Faults - Ab Ghani, Sharin; Mohd Hambali, Roslan; Yusuf Lada, Musa; Ahmad Khiar, Mohd Shahril (2013)
Sweep Frequency Response Analysis (SFRA) is well known power transformer diagnostics device which capable on detected faults/changes either electrical or mechanical. However the challenges are on understanding the SFRA results for the newcomers’ engineers. If wrong, mislead interpretation of SFRA results would arise. Inline of this matter, five transformers model with simulated faults have been developed. The faults are; Core Damage, Shorted Turns, Open Circuit, Radial Deformations (Hoop Buckling) and Axial Displacement. These faults are designed to imitate the actual faults occurred in power transformer. Hence, the SFRA is then applied to the models to visualize the changes of SFRA results. In fact it create a clear understanding of the SFRA results changes with referring to which faults occurred.